Activities of the summer party of the 23rd Japanese Antarctic Research Expedition in 1981-1982 - Shinji Mae (National Institute of Polar Research, 1983)
This report outlines the summer activities of the 23rd Japanese Antarctic Research Expedition (JARE-23) in 1981-1982. JARE-23 comprised 34 wintering persons led by Dr. Takao HOSHIAI and 10 men of the summer party led by the present author. A Japanese observer participated in the summer activities. An Australian exchange scientist under the Antarctic Treaty provisions, Mr. G. A. DUFF, jointed the summer party between Fremantle, Australia and Port Louis, Mauritius. The relief ship, icebreaker FUJI, left Tokyo on November 25,1981,carrying about 500 tons of cargo. After calling at Fremantle between December 11 and 16,she arrived at the edge of pack ice on December 31,1981. The transportation of cargo and personnel to and from Syowa Station was carried out between January 4 and February 11,1982. After the accomplishment of field operations in the Syowa Station area, FUJI visited Molodezhnaya Station and Amundsen Bay. Then she returned to Tokyo on April 20,1982 via Port Louis (March 11 to 17) and Singapore (April 1 to 8). The observation of ionosphere and the studies on the physical, chemical and biological oceanography were performed on board. At Syowa Station, studies on moss ecology and oceanographical observations in the ice-covered sea were carried out. Geological and geodetic surveys were made in the ice-free areas of the Soya Coast. A party was dispatched to Mizuho Station from January 14 to 24 for the exchange of personnel and resupply of materials to winter in 1982. Concurrently the basement of a new power station (about 290m^2) was constructed. An existing 130kl water tank which was located in the construction area of the new power station was removed and a 100kl water tank was set. At Molodezhnaya Station, USSR-Japan cooperative research on upper atmosphere physics was carried out and geological and biological samples were collected. In the Amundsen Bay area, geological, geomorphological, gravimetric and biological surveys were made with the cooperation of the 22nd Wintering Party. During the cruise to Port ...